Defeminisasi dalam Penggunaan Ragam Bahasa Jepang: Studi Kasus Maomao dalam Anime Kusuriya no Hitorigoto Season 1 - Ginanjar, Pika Yestia; Herawati, Isye (KIRYOKU, 2026)
This study aims to describe the phenomenon of defeminization in the use of Japanese Speech Style. The term defeminization in this study is adopted from Okamoto (1995, 1996), referring to the phenomenon of diminishing or devaluing an individual's feminine attributes. Defeminization not only occurs in role or yakuwarigo but also represents a widespread social phenomenon in Japanese society. In the anime Kusuriya no Hitorigoto season 1, defeminization is identified through the speech style of the main female character, Maomao. The data showed that Maomao does not use feminine forms, especially when using final particles, despite her gender. This study employed a sociolinguistic approach to examine the contextual meaning of Maomao's utterances that demonstrate defeminization, and it also considered Maomao's social interactions as a factor influencing her choice of speech style. Data was collected through recordings and transcriptions from Netflix. The research revealed that Maomao used vowel coalescence in -shitee (shitai), final sentence endings such as -dayo and -daro, command forms like -shiro), and terms like oyaji as an address form, which are recognized as non-feminine forms. Additionally, Maomao's birth circumstances and environment in Kusuriya no Hitorigoto contribute to the occurrence of defeminization.